Gravitational search algorithm-based UPQC for power quality improvement of WECS. (20th February 2020) - Anitha, R.; Jeyadevi, S.
The design of merged presentation of UPQC and WECS is conscientious for extenuating the PQ problems of distribution scheme in the work. The projected scheme is unruffled of WECS, sequences and shunt APF joined to DC link that is capable to compensate the voltage sag, swell, harmonics and voltage interruption. Currently, the recompense approach of UPQC is examined with GSA. Here, GSA is engaged to enhance the control pulses of UPQC. To acquire optimal performance of the distribution system, these faults are diminished and producing the optimal control signals. The expected scheme is capable to bring in the active power to grid also its competence in augmentation of power quality in distribution scheme. The presentation of the expected GSA-based UPQC scheme is corroborated over simulations by MATLAB/Simulink and compared with the traditional approaches such as ANFIS-based UPQC and GA-based UPQC.